ON BOUNDARY CONDITION BY DIFFRACTION OF HARMONIC WAVE ON THE INFINITE INCLUSION - Karakhanian, I. M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
In the given article the jump type boundary condition is proved, which was considered in a boundary problem discussed in [1], connected with a harmonic wave diffraction on the half-infinite inclusion.